Hormonal profile of pubertal age girls with chronic viral hepatitis - E. F. Chaykivska (Kazimierz Wielki University, 2020)
Chronic viral hepatitis (CVH) is more than 70% of the total number of children with chronic hepatitis, and in the population - 0.5%. Adolescents are the most vulnerable group of the population due to the physiological and psychological characteristics of this age. The liver coordinates both adaptive and reproductive processes in the body, and during puberty is the formation of pituitary-gonadal relationships. The aim: to study the features of hormonal homeostasis in adolescent girls with CVH. Materials and methods. We examined 300 girls aged 12-17 years, of which 120 patients with CVH (60 patients with hepatitis B and 60 - with hepatitis C) and 180 relatively healthy patients with physiological sexual development. The diagnosis of CVH was established on the basis of medical history, clinical, virological, biochemical, morphological and instrumental examination. Results. Analysis of the obtained data of the functional state of the liver in the examined patients with CVH revealed disorders of the morphofunctional state of the liver, manifested by cytolysis syndrome, cholestasis, hepatocellular insufficiency and mesenchymal-inflammatory syndrome. In patients with CVH there was a decrease in the production of luteinizing hormone (4.35 ± 0.09 vs. 5.13 ± 0.08 mIU / ml, p<0.01); follicle-stimulating hormone (4.40 ± 0.15 vs. 5.40 ± 0.07 mIU / l, p<0.01); prolactin (215.56 ± 4.76 vs. 282.93 ± 8.36 mIU / ml, p <0.01); progesterone (2.09 ± 0.10 vs. 2.78 ± 0.08 nmol / l, p<0.01) on the background of increasing the average level of estradiol (468.65 ± 21.32 vs. 437.45 ± 9.59 pmol / l, p<0,01) and free testosterone (1,98 ± 0,08 vs. 1,16 ± 0,04 nmol / l, p <0,01). Thyroid status was characterized by a relative decrease in the production of thyroid-stimulating hormone (1.74 ± 0.04 vs. 2.15 ± 0.05 μIU / ml (p<0.01) and an increase in the secretion of free triiodothyronine (9.32 ± 0.09 vs. 5,46 ± 0.07 pmol / l, p<0.01) and free thyroxine (23.35 ± 0.76 vs. 18.55 ± 0.20 pmol / l, p<0.01). chronic infectious process, affects the morphofunctional state of the liver and leads to dysfunction of the hypothalamic-pituitary-ovarian and pituitary-thyroid systems, manifested by pathological changes in the secretion of gonadotropins, prolactin, thyroid-stimulating hormone, sex steroids and hormonal steroids.